Inflammatory Biomarkers, Death, and Recurrent Nonfatal Coronary Events After an Acute Coronary Syndrome in the MIRACL Study. Issue 1 (28th January 2013) - Zamani, Payman; Schwartz, Gregory G.; Olsson, Anders G.; Rifai, Nader; Bao, Weihang; Libby, Peter; Ganz, Peter; Kinlay, Scott; ,
Abstract : Background: In acute coronary syndromes, C‐reactive protein (CRP) strongly relates to subsequent death, but surprisingly not to recurrent myocardial infarction. Other biomarkers may reflect different processes related to these outcomes. We assessed 8 inflammatory and vascular biomarkers and the risk of death and recurrent nonfatal cardiovascular events in the 16 weeks after an acute coronary syndrome. Methods and Results: We measured blood concentrations of CRP, serum amyloid A (SAA), interleukin‐6 (IL‐6), soluble intercellular adhesion molecule (ICAM), soluble vascular cell adhesion molecule (VCAM), E‐selectin, P‐selectin, and tissue plasminogen activator antigen (tPA) 24 to 96 hours after presentation with acute coronary syndrome in 2925 subjects participating in a multicenter study. Biomarkers were related to the risk of death, and recurrent nonfatal acute coronary syndromes (myocardial infarction or unstable angina) over 16 weeks using Cox proportional hazard models. On univariate analyses, baseline CRP ( P =0.006), SAA ( P =0.012), and IL‐6 ( P <0.001) were related to death, but not to recurrent nonfatal acute coronary syndromes. VCAM and tPA related to the risk of death ( P <0.001, P =0.021, respectively) and to nonfatal acute coronary syndromes ( P =0.021, P =0.049, respectively). Adjusting for significant covariates reduced the strength of the associations; however, CRP and SAA continued to relate to death. Conclusions: In acute coronary syndromes, the CRP inflammatory axis relates to the risk of death and may reflect myocardial injury. VCAM and tPA may have greater specificity for processes reflecting inflammation and thrombosis in the epicardial arteries, which determine recurrent coronary events.